Soil Contamination and Alternatives for Sustainable Development 2019
DOI: 10.5772/intechopen.82192
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Tests as a Tool to Assess the Quality of the Soil

Abstract: Terrestrial ecotoxicology is used to evaluate the effects of substances that, whenever added to the soil, have impact on organisms and help measuring the responses from changes in the lethality, reproduction, development, and behavior of standardized soil organisms. Terrestrial ecotoxicology is a new tool that has been introduced in many countries, including Brazil, and yet little used. However, it is already widely used in Europe, besides being mandatory in research to indicate the toxicity of waste discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Ecotoxicity tests are rapid tests commonly used to determine the impact of contaminants on living organisms (Clasen and Lisbôa 2019 ). The obtained data on ecotoxicity revealed that the formation of one or more metabolites could induce acute toxicity despite a significant reduction in parent compound concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Ecotoxicity tests are rapid tests commonly used to determine the impact of contaminants on living organisms (Clasen and Lisbôa 2019 ). The obtained data on ecotoxicity revealed that the formation of one or more metabolites could induce acute toxicity despite a significant reduction in parent compound concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In order to predict how substances impact on soil-dwelling organisms, and the potential damage to soil ecosystems [102], special toxicity studies on representative terrestrial organisms can be carried out. Edaphic organisms are the most widely used biomodel to evaluate the quality of soil; they are important because of their functions in decomposition, cycling, and regularization of nutrients in biological systems [103,104].…”
Section: Terrestrial Biomodelsmentioning
confidence: 99%
“…Several papers show the toxicity of organic pollutants [103,104], domestic effluents [105], hydrocarbons [106], solvents from biomass [25], and heavy metals [107] in terrestrial environments. However, no existing literature on terrestrial toxicity has been found.…”
Section: Terrestrial Biomodelsmentioning
confidence: 99%
“…According to the World Bank Report [1], the amount of municipal solid waste (MSW) generated across South Asia, Latin America, and Sub-Saharan Africa will double or triple by the year 2050, making up 35% of the global MSW. MSW is among several human activities that have exposed the environment to many toxic substances [2], causing the various degree through robust parameters such as contamination factors (CF), geo-accumulation indexes (Igeo), and enrichment factors (EF) [31]. Similarly, human health risk is assessed through cancer risk (CR) and hazard index (HI) parameters as a means to ascertain the possible carcinogenic and non-carcinogenic risks to humans, respectively [24].…”
Section: Introductionmentioning
confidence: 99%